Association between metabolic syndrome and sensorineural hearing loss: a cross-sectional study of 11,114 participants - Aghazadeh-Attari J (Dove Medical Press, 2017)
Javad Aghazadeh-Attari,1 Behnam Mansorian,2 Mohammad Mirza-Aghazadeh-Attari,3 Jamal Ahmadzadeh,2 Iraj Mohebbi2 1Social Determinants of Health Research Center, Department of Neurosurgery, 2Social Determinants of Health Research Center, Occupational Medicine Center, Urmia University of Medical Sciences, Urmia, 3Medical Philosophy and History Research Center, Tabriz University of Medical Sciences, Tabriz, Iran Background/objectives: Hearing loss (HL) is associated with certain diseases and affects health, resulting in a low quality of life. Some components of the metabolic syndrome (MetS) coincide with the risk factors for sensorineural hearing loss (SNHL). To date, very few studies have examined the link between MetS and HL. The aim of the current study was to try to understand the potential association between MetS and HL.Methods: Using Iranian health surveys of professional drivers, we enrolled 11,114 individuals aged 20–60 years, whose main job is to operate a motor vehicle. We examined participants for the presence and absence of SNHL and the components of the MetS. Additionally, we investigated the relationship between MetS and the pure tone air conduction hearing thresholds of participants with SNHL, including low-frequency and high-frequency thresholds.Results: This cross-sectional study consisted of 11,114 participants: 3202 (28.81%) diagnosed with MetS and 7911 (71.18%) without and 2772 (24.94%) with SNHL and 8432 (75.86%) without. Participants with SNHL had a higher number of components of MetS (P<0.001 for all components).Conclusion: Our results demonstrated that an association possibly exists between different components of MetS (obesity, hypertension, hypertriglyceridemia, high fasting glucose levels, and waist circumference) and SNHL in a population of West Azerbaijan drivers. Therefore, it is important to schedule periodic checkups for drivers to detect and avoid the increase in MetS components at an early stage in this population. Keywords: metabolic syndrome, obesity, sensorineural hearing loss, a cross-sectional study